OBE implementation and design of continual quality improvement (CQI) for accreditation of biomedical engineering program University of Malaya - Karman, Salmah; Hasikin, Khairunnisa; Ting, Hua Nong; Ng, Siew Cheok; Wahab, Ahmad Khairi Abdul; Lim, Einly; Hamzaid, Nur Azah; Wan Abas, Wan Abu Bakar (2011)
This paper describes the outcome based education (OBE) implementation and continuous quality improvement (CQI) process plan in the Department of Biomedical Engineering, University of Malaya. The implementation of CQI plan is a part of the Outcome - based Education (OBE) approach required by the Engineering Accreditation Council (EAC) for recognition of Biomedical Engineering program and as a graduate student for Board of Engineer Malaysia (BEM) and Institute of Engineer Malaysia (IEM) membership registration. This approach was first introduced to Biomedical Engineering Department since 2005. The measurement on Programme Outcomes (POs) which will be evaluated upon graduation is done based on the results of sub-Programme Outcome (subPOs) which are evaluated at the end of each course. The improvement on assessment and evaluation process are continuously done to obtain the better achievement of POs and programme educational objectives (PEO)s in the department of Biomedical Engineering.